2021
DOI: 10.1038/s42003-021-02630-z
|View full text |Cite
|
Sign up to set email alerts
|

Prenylcysteine oxidase 1, an emerging player in atherosclerosis

Abstract: The research into the pathophysiology of atherosclerosis has considerably increased our understanding of the disease complexity, but still many questions remain unanswered, both mechanistically and pharmacologically. Here, we provided evidence that the pro-oxidant enzyme Prenylcysteine Oxidase 1 (PCYOX1), in the human atherosclerotic lesions, is both synthesized locally and transported within the subintimal space by proatherogenic lipoproteins accumulating in the arterial wall during atherogenesis. Further, Pc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 73 publications
1
32
0
1
Order By: Relevance
“…PCYOX1 has recently emerged as a lipoprotein-associated protein, representing a potential novel member in the panel of oxidant enzymes involved in the pathogenesis of atherosclerosis [ 7 ]. Its biological functions have thus extended from the former findings by Casey’s group who described PCYOX1 as a lysosomal enzyme involved in the catabolism of prenylated proteins [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…PCYOX1 has recently emerged as a lipoprotein-associated protein, representing a potential novel member in the panel of oxidant enzymes involved in the pathogenesis of atherosclerosis [ 7 ]. Its biological functions have thus extended from the former findings by Casey’s group who described PCYOX1 as a lysosomal enzyme involved in the catabolism of prenylated proteins [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…PCYOX1 is a flavin adenine dinucleotide (FAD)-dependent thioether oxidase that produces free cysteine, an isoprenoid aldehyde, and a stoichiometric amount of hydrogen peroxide [ 10 ]. Our previous study identified PCYOX1 as a novel member in the panel of oxidant enzymes involved in the pathogenesis of atherothrombosis [ 7 ]. Being a FAD-dependent thioether oxidase distinguishes it from other oxidant enzymes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations